Fronteiras e caminhos-de-ferro - Pereira, Hugo Silveira (2018)
The Portuguese technocratic elites who, in mid-19th century, supported Fontismo were largely inspired by the Saint-simonianist ideology, developed in France in the late 18th and early 19th centuries. Saintsimonianism argued for the creation of civilizations of circulation that could foster a European federation, through the construction of railway networks, drawing different nations closer together. Portuguese engineers and politicians assimilated this ideology that was in the base of the project of connecting Porto, Lisbon and sundry overseas territories to its neighbouring countries and regions. However, this plan clashed against opposing economic, political and diplomatic agendas of those nations. Using the concept of technodiplomacy and the models of cross-borders and transnational large technological systems (LTS), we aim to show how the Saint-simonianist project of creation of civilizations of circulation was hindered by the appearance of technodiplomatic obstacles. We hope to contribute to the debate about transnational LTS.